Strategies in Global Competition : Selected Papers from the Prince Bertil Symposium at the Institute of International Business. - Hood, Neil (Routledge Library Editions: International Business., 2013)
The main thrust of Part 1 is to give some understanding of the concept of 'global competition'. In doing so, the chapters rely heavily on industrial studies. Part 2 deals with two different aspects of this change viewed from two different perspectives. The one is economic and more macro: the other political and social and more micro, being concerned with the way in which companies have to utilize their various organisational units and integrate information on a fragmented environment into a strategic whole. Part 3 deals specifically with technology, as the particular segment of the environment.